T3 and T4 autoantibodies: emerging biomarkers for evaluating thyroid disorders - Liu, Jiameng; Mao, Chaoming; Mao, Xueqian; Wang, Xi; Zheng, Tingting; Dong, Liyang; Mao, Yufei (Frontiers in Endocrinology, 2025)
Introduction and objectivesThe clinical significance of thyroid hormone autoantibodies, specifically triiodothyronine autoantibodies (T3-Ab) and thyroxine autoantibodies (T4-Ab), is not well understood due to current detection method limitations. This study investigated the clinical utility of T3-Ab and T4-Ab as biomarkers for thyroid function by developing a Magnetic Chemiluminescent Immunoassay (MCLIA) kit.MethodsA chemiluminescent immunoassay kit was developed using magnetic nanomicroparticles conjugated with T3 or T4 antigens. An indirect detection approach (magnetic microparticle antigen-target antibody-anti-human IgG antibody) was employed. Reference ranges were established using 415 serum samples from healthy individuals. Additionally, serum samples from 1,654 patients with various diseases were analyzed for T3-Ab and T4-Ab distribution levels and positive rates. Mass spectrometry and recovery experiments assessed potential interference of T3-Ab and T4-Ab with thyroid hormone detection.ResultsThe validation process confirmed the efficacy of the MCLIA kit in detecting serum T3-Ab and T4-Ab. The reference ranges for both antibodies were set at ≤ 1.0 AU/mL and showed no significant correlations with other thyroid markers, including FT3, FT4, TSH, TG, TG-Ab, TPO-Ab, or TR-Ab. Notably, T3-Ab and T4-Ab levels interfered with FT3 and FT4 detection, especially in competitive chemiluminescent immunoassays. Elevated levels of T3-Ab and T4-Ab were found in patients undergoing immune checkpoint blockade therapy.ConclusionsThis study presents the first MCLIA kit for detecting T3-Ab and T4-Ab in human serum, revealing their potential as thyroid disorder biomarkers, particularly in cancer patients undergoing immune checkpoint blockade therapy, where they interfere with thyroid hormone measurements.